Inappropriate end-of-life cancer care in a generalist and specialist palliative care model: a nationwide retrospective population-based observational study. Issue Volume 12(2022)Issue e1 (22nd December 2020) - Boddaert, Manon S; Pereira, Chantal; Adema, Jeroen; Vissers, Kris C P; van der Linden, Yvette M; Raijmakers, Natasja J H; Fransen, Heidi P
Abstract : Objectives: To evaluate the impact of provision and timing of palliative care (PC) on potentially inappropriate end-of-life care to patients with cancer in a mixed generalist—specialist PC model. Method: A retrospective population-based observational study using a national administrative health insurance database. All 43 067 adults in the Netherlands, who were diagnosed with or treated for cancer during the year preceding their death in 2017, were included. Main exposure was either generalist or specialist PC initiated >30 days before death (n=16 967). Outcomes were measured over the last 30 days of life, using quality indicators for potentially inappropriate end-of-life care. Results: In total, 14 504 patients (34%) experienced potentially inappropriate end-of-life care; 2732 were provided with PC >30 days before death (exposure group) and 11 772 received no PC or ≤30 days before death (non-exposure group) (16% vs 45%, p<0.001). Most patients received generalist PC (88%). Patients provided with PC >30 days before death were 5 times less likely to experience potentially inappropriate end-of-life care (adjusted OR (AOR) 0.20; (95% CI 0.15 to 0.26)) than those with no PC or PC in the last 30 days. Both early (>90 days) and late (>30 and≤90 days) PC initiation had lower odds for potentially inappropriate end-of-life care (AOR 0.23 and 0.19, respectively). Conclusion: Timely access to PC in a mixed generalist—specialist PC model significantly decreases the likelihood of potentially inappropriate end-of-life care for patients with cancer. Generalist PC can play a substantial role.